2017
DOI: 10.3390/ijerph14091083
|View full text |Cite
|
Sign up to set email alerts
|

Green Space and Depression during Pregnancy: Results from the Growing Up in New Zealand Study

Abstract: Background: Antenatal depression is an important contributor to poor maternal health experienced by some women. This study aimed to determine whether exposure to green space during pregnancy is associated with less depression, and whether this association is moderated by relevant factors, such as age, education, self-identified ethnicity, physical activity, residential rurality, and socioeconomic status. Methods: Health data were sourced from the cohort study "Growing Up in New Zealand" comprised of 6772 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
1
22
0
1
Order By: Relevance
“…Mukherjee et al (2017) showed that park size was significantly negatively associated with depression even when models were adjusted for confounders such as income, education or employment status, but also for age, gender, marital status and household composition. Similarly, Calogiuri et al (2016) and Nichani et al (2017) found that socio-economic inequality in mental well-being was significantly lower among respondents reporting good access to a green space compared with those who had less access. Other studies, however, could not find any relationship between health outcome and socio-economic or socio-demographic confounders (Calogiuri et al 2016;Nichani et al 2017) or showed that significant associations between green space and health outcome became non-significant after models were adjusted for confounders (Cusack et al 2017;Richardson et al 2017a).…”
Section: Confounding Factorsmentioning
confidence: 93%
See 2 more Smart Citations
“…Mukherjee et al (2017) showed that park size was significantly negatively associated with depression even when models were adjusted for confounders such as income, education or employment status, but also for age, gender, marital status and household composition. Similarly, Calogiuri et al (2016) and Nichani et al (2017) found that socio-economic inequality in mental well-being was significantly lower among respondents reporting good access to a green space compared with those who had less access. Other studies, however, could not find any relationship between health outcome and socio-economic or socio-demographic confounders (Calogiuri et al 2016;Nichani et al 2017) or showed that significant associations between green space and health outcome became non-significant after models were adjusted for confounders (Cusack et al 2017;Richardson et al 2017a).…”
Section: Confounding Factorsmentioning
confidence: 93%
“…Similarly, Calogiuri et al (2016) and Nichani et al (2017) found that socio-economic inequality in mental well-being was significantly lower among respondents reporting good access to a green space compared with those who had less access. Other studies, however, could not find any relationship between health outcome and socio-economic or socio-demographic confounders (Calogiuri et al 2016;Nichani et al 2017) or showed that significant associations between green space and health outcome became non-significant after models were adjusted for confounders (Cusack et al 2017;Richardson et al 2017a). For example, Padilla et al (2016) showed that the significant association between green space and stress disappeared when models were adjusted for socioeconomic confounders.…”
Section: Confounding Factorsmentioning
confidence: 93%
See 1 more Smart Citation
“…We examined the effect sizes corresponding to 300 m or the closest buffer size reported, since it captures residential greenness, and also it allowed comparability between studies. A study [37] that measured green space percentage in census unit and did not define buffer distances was also included. Effect estimates based on continuous NDVI were included when other types of exposure (e.g., Q4 vs. Q1) were also reported [10,38].…”
Section: Meta-analysismentioning
confidence: 99%
“…Some studies considered the distance to major green spaces in the neighbourhood, either by calculating the linear distance [38,[49][50][51][52][53] or by using street network buffer based on walkable distances [40,49,50,54]. Some studies [27,37,[44][45][46][55][56][57][58][59] used the proportion of green/natural spaces in the total area of census block or zip code as a surrogate for greenness exposure. A number of studies [27,45,51,56] considered public green spaces, while one [46] also included private greenness (e.g., private gardens) in the analysis.…”
Section: Exposure Variablesmentioning
confidence: 99%